Dinâmica monetária eficiente sob encontros aleatórios: uma classe de métodos numéricos que exploram concavidade - Bertolai, Jefferson Donizeti Pereira (2009)
The dificulty in characterizing non-stationary allocations or equilibria is one of the main explanations for the use of concepts and assumptions that trivialize the dynamics of the economy. This difficulty is especially critical in Monetary Theory, in which the dimensionality of the problem is high even for very simple models. In this context, this paper reports the computational strategy for implementing the recursive method proposed by Monteiro and Cavalcanti (2006), which allows you to calculate the optimal sequence (possibly non-stationary) of distributions of money in an extension of the model proposed by Kiyotaki and Wright (1989). Three aspects of this calculation are emphasized: (i) the computational implementation of the plannerís problem involves the choice of continuous and discrete variables that maximize a nonlinear function and satisfies nonlinear constraints; (ii) the objective function of this problem is not concave and constraints are not convex, and (iii) the set of admissible choices is not known a priori. The goal is to document the difficulties involved, the proposed solutions and available methods and resources to implement the numerical characterization of efficient monetary dynamics under the assumption of random matching.